Considerations For a Malaysian Cradle-To-Grave Identification Proposal - Tee, Elok Robert (Malaysian Journal of Computer Science, 1997)
Presents a model for a Malaysian CGID and broadly reviews its requirements and issues in authentication, data storage, security, authorization, duplication and recovery.